Inventory of chiton species (Polyplacophora) from the rocky intertidal of the Northern Gulf of California, with an illustrated taxonomic key - Reyes-Gómez, Adriana; Vargas-Ponce, Ofelia; Galván-Villa, Cristian; Barragán, José Salgado-; Esqueda-González, Ma. Del Carmen; Ríos-Jara, Eduardo (Zootaxa, 2023)
This work presents an inventory of the Polyplacophora species registered in December 2019 in the intertidal environment of 10 sampling sites of the Northern Gulf of California, México. Fifteen species were obtained from a total of 33 species previously reported throughout the Gulf. Acanthochitona avicula, Ischnochiton guatemalensis, Lepidozona serrata, and Dendrochiton lirulatus are rare with only 1 to 3 specimens recorded of each species. Stenoplax mariposa and Lepidozona subtilis were the most abundant with 162 and 284 specimens, respectively. Acanthochitona avicula, I. guatemalensis, Lepidozona serrata, and Lepidochitona beanii are rare and each was only recorded at one sampling site. For a better recognition of these species, we provide a dichotomous identification key, which is complemented with high-resolution photographs and images obtained by scanning electron microscopy. In addition, habitat data and taxonomic comments are included to facilitate a better understanding of the habitat preferences, relationships and current taxonomic position of these species.